Single entity electrochemistry for the elucidation of lithiation kinetics of TiO2 particles in non-aqueous batteries. (March 2019) - Löffler, Tobias; Clausmeyer, Jan; Wilde, Patrick; Tschulik, Kristina; Schuhmann, Wolfgang; Ventosa, Edgar
Abstract: In battery research, the development of analytical techniques is of key importance for determining intrinsic properties of active materials ultimately dictating the battery performance. We report the application of nano-impact electrochemistry to gain insight into the intrinsic properties of commercial battery materials i.e. TiO2 particles in non-aqueous media. Potentiostatic lithiation measurements do not only provide qualitative information about the rate-limiting step in the lithiation process, but also demonstrate that nano-impact electrochemistry is a suitable technique in non-aqueous media in complete absence of oxygen and water. Our results reveal that the intrinsic lithiation rate of individual TiO2 particles is not – as generally assumed – determined by interfacial ion transfer kinetics, mobility of ion and/or electrons in the bulk of the particle, but by the solid-solid electron transfer. These findings have important implications for future studies of fundamental properties of battery materials considering that charge transfer in battery electrodes does not always obey Butler-Volmer kinetics. Graphical abstract: fx1 Highlights: Nano-impact electrochemistry provides insight into the intrinsic properties of commercial battery materials. Nanoimpact electrochemistry is a suitable technique also for non-aqueous media in absence of oxygen and water. The intrinsic lithiation rate of individual TiO2 particles is not determined by ion transfer kinetics or bulk diffusivity. The intrinsic lithiation rate of individual TiO2 particles is determined by solid-solid electron transfer.